Antibacterial Synergy Detection of Lignin Extract from Oil Palm Empty Fruit Bunches (Opefb) Combined with Amoxicillin Against Staphylococcus Aureus Using The Azdast Method - Hendri, Rifki Anshory; Suryadi, Herman; Hayun, Hayun (Green Engineering Society, 2024)
Oil palm empty fruit bunches (OPEFB) are waste generated by the palm oil industry and are generally considered an environmental problem due to their large quantity and difficult recyclability. This study's objective was to examine the potential of OPEFB lignin extract combined with amoxicillin in inhibiting the growth of Staphylococcus aureus bacteria. The Synergism Test of the OPEFB lignin extract-antibiotic combination was conducted using the AZDAST method (Ameri Ziaei Double Antibiotic Synergism Test). The lignin extraction process was a steam process using a 4% oxalic acid solution under optimal conditions. Then, Calcium ions precipitate 4% oxalate by adding Ca(OH)2 to the extract. The Lignin content was determined by UV-Vis spectrophotometry at 280 nm, and then the lignin extract was combined with antibiotics for antibacterial assay. The results showed a lignin content of 1.06 %. The AZDAST test results revealed clear zones from the combination of OPEFB lignin extract and amoxicillin with a diameter of 20.23 mm for the extract containing oxalate and 15.83 mm for the oxalate-free extract. Meanwhile, on average, the clear zone of single amoxicillin was only 14.13 mm. Based on these results, the combination of OPEFB lignin extract with amoxicillin was stronger than amoxicillin alone in inhibiting the growth of S. aureus, but it was not significantly different (p-value> 0.05). In conclusion, the potential of OPEFB lignin extract synergistically worked with the antibiotic amoxicillin in inhibiting the growth of S. aureus.